1982
DOI: 10.1007/bf00423094
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine receptors in canine caudate nucleus

Abstract: This study was done to obtain direct in vitro evidence for the possible existence of more than one type of dopaminergic binding site in homogenates of the caudate nucleus from calf brain. Five radioligands for dopaminergic sites were tested. The inhibitions of two agonist radioligands ([3H]dopamine, [3H]apomorphine) by haloperidol, chlorpro-mazine, or piflutixol were biphasic. The inhibitions of [3H-haloperidol, [3H]spiroperidol, and [3Hldihydroergocryptine binding by dopamine and (-)-norepinephrine were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 85 publications
2
29
0
Order By: Relevance
“…Conversely, administration of a D 2 agonist attenuates and D 2 antagonist facilitates cortical inputs without affecting limbic inputs [33], indicating that (i) limbic inputs are selectively modulated by D 1 -receptor stimulation, (ii) cortical inputs are selectively modulated by D 2 -receptor stimulation and (iii) low baseline concentration of DA tonically attenuates cortical input via D 2 -receptor stimulation. This is consistent with DA-receptor-binding assays showing that D 2 receptors exhibit higher affinity for DA than do the D 1 receptors [34]. …”
Section: Da-system Modulation Of the Naccsupporting
confidence: 88%
“…Conversely, administration of a D 2 agonist attenuates and D 2 antagonist facilitates cortical inputs without affecting limbic inputs [33], indicating that (i) limbic inputs are selectively modulated by D 1 -receptor stimulation, (ii) cortical inputs are selectively modulated by D 2 -receptor stimulation and (iii) low baseline concentration of DA tonically attenuates cortical input via D 2 -receptor stimulation. This is consistent with DA-receptor-binding assays showing that D 2 receptors exhibit higher affinity for DA than do the D 1 receptors [34]. …”
Section: Da-system Modulation Of the Naccsupporting
confidence: 88%
“…Reynolds et al (2001) and Reynolds and Wickens (2002) proposed a similar theory to explain D2 receptor dependent LTD and D1 receptor-dependent LTP at corticostriatal synapses. Our data support these theories because 1) LTP is enhanced when 3-NP reduces dopamine release in the striatum and 2) exogenous addition of dopamine or the D2 receptor agonist quinpirole eliminates the 3-NP enhanced LTP and increases LTD. More LTP is seen in the dorsomedial striatum as are more D1 receptors and thus, when dopamine is reduced it has a greater probability of binding to D1 receptors (Ariano et al, 1989; Maeno, 1982; Partridge et al, 2000; Smith et al, 2001). By contrast, normal dopamine release in control slices or addition dopamine to dopamine-depleted brain slices increases the probability of dopamine binding to D2 receptors, which increases LTD expression at corticostriatal synapses (Akopian and Walsh, 2006; Calabresi et al, 1992; Kreitzer and Malenka, 2007; Wang et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, our selection of the dorsomedial striatum increased the likelihood of D1 receptor participation over D2 receptors (Ariano et al, 1989; Maeno, 1982). Wang et al (2006) found dopamine triggers D2 receptor-dependent LTD by acting presynaptically to reduce acetyl choline (ACh) release from cholinergic interneurons.…”
Section: Discussionmentioning
confidence: 99%
“…MSNs, and D2R is predominantly expressed in the enkephalin (coded by Penk gene)-expressing MSNs; each type of MSNs constitutes the direct and indirect pathways, respectively, in the NAc (3). As the affinity for DA is much higher for the D2R (nM order) than for the D1R (μM order) (22,23), a reduction in DA levels is thought to result in the inactivation of G i -coupled D2R but to have no appreciable effect on the D1R (3, 24), thereby up-regulating the neural activity specifically in the indirect pathway. Moreover, the Fos activation was more prominently observed in Penk-or Drd2 (D2R)-expressing cells than in the Tac1-or Drd1a (D1R)-expressing cells (Fig.…”
Section: Up-regulation Of Fos Gene Expression By Optical Inactivationmentioning
confidence: 99%